2019
DOI: 10.1111/1475-6773.13196
|View full text |Cite
|
Sign up to set email alerts
|

Competition and health plan quality in the Medicare Advantage market

Abstract: Objective To examine the relationship between insurer market structure, health plan quality, and health insurance premiums in the Medicare Advantage (MA) program. Data Sources/Study Setting Administrative data files from the Centers for Medicare and Medicaid Services, along with other secondary data sources. Study Design Trends in MA market concentration from 2008 to 2017 are presented, alongside logistic and linear regression models examining MA plan quality and premiums as a function of insurer market struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Recent trends with respect to the increased use of telehealth across all insurance markets may be an important part of the solution 19 . Similarly, our finding that more concentrated MA markets have more restrictive networks illustrates potential harm from the relatively concentrated nature of MA markets 20 …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recent trends with respect to the increased use of telehealth across all insurance markets may be an important part of the solution 19 . Similarly, our finding that more concentrated MA markets have more restrictive networks illustrates potential harm from the relatively concentrated nature of MA markets 20 …”
Section: Discussionmentioning
confidence: 63%
“…19 Similarly, our finding that more concentrated MA markets have more restrictive networks illustrates potential harm from the relatively concentrated nature of MA markets. 20 Second, our results underscore the importance of improving the accuracy of provider network data and developing alternative measures of network restrictiveness. Prior work relying on provider directories, 4 for instance, found that cardiology networks were narrower than other specialties, contrary to our results.…”
Section: Discussionmentioning
confidence: 75%